Influence of surface form deviations on friction in mixed lubrication. (February 2018) - Fricke, S.; Hager, C.; Solovyev, S.; Wangenheim, M.; Wallaschek, J.
Abstract: The focus of this study is on the effect of form deviations of a partial journal bearing's sliding surface on the friction force in mixed lubrication conditions. The measured friction varied considerably when the bearing was rotated in the opposite direction at the same speed and normal load. This unexpected observation motivated the presented simulation study. The overall form deviations of the surface of the test bearing were measured with white light interferometry and used as simulation input. The two-scale simulation approach considers the effect of the surface roughness on a microscopic and the global bearing geometry with the surface form deviations on a macroscopic scale. Simulation results show that the surface form deviations can have a noticeable effect on the pressure distribution of the lubricant and hence on the size of the asperity contact area which leads to the differences in friction. The influence of the lubricant viscosity, the clearance gap and the surface roughness were analysed in a parametric simulation study. Results show that the clearance and the surface roughness control the impact of the surface form deviations on the friction force. All in all, the results show the necessity to include all scales of surface form deviations in the simulation of journal bearings in a mixed lubrication regime. Highlights: The impact of roundness deviations of a journal bearing on mixed friction is analyzed with simulation and experiment. The measured roundness deviations considered in simulation influence the computed hydrodynamic pressure build-up. Comparison shows a good coincidence of simulation and experiment.